To the cloud : cloud powering an enterprise - Arora, Pankaj; Biyani, Raj; Dave, Salil (McGraw Hill, 2012)
This insider's guide offers a concise framework and tested best practices for migrating IT to the cloud, based on Microsoft's own journey moving its internal systems